2012
DOI: 10.1007/s00253-012-4564-4
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities related to volatile organic compound emission in automobile air conditioning units

Abstract: During operation of mobile air conditioning (MAC) systems in automobiles, malodours can occur. We studied the microbial communities found on contaminated heat exchanger fins of 45 evaporators from car MAC systems which were operated in seven different regions of the world and identified corresponding volatile organic compounds. Collected biofilms were examined by scanning electron microscopy and fluorescent in situ hybridization. The detected bacteria were loosely attached to the metal surface. Further analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…The genus-level analysis of bacterial 16S rRNA gene sequences showed that members of the genus Methylobacterium (phylum Proteobacteria) were predominantly identified from all samples, in agreement with the results from previous studies (3,6). However, their relative abundances were highly varied, with a range of 3.3% to 79.4% of the total bacterial sequences depending on the samples.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The genus-level analysis of bacterial 16S rRNA gene sequences showed that members of the genus Methylobacterium (phylum Proteobacteria) were predominantly identified from all samples, in agreement with the results from previous studies (3,6). However, their relative abundances were highly varied, with a range of 3.3% to 79.4% of the total bacterial sequences depending on the samples.…”
Section: Resultssupporting
confidence: 89%
“…Microbial diversity analysis showed that bacterial communities in the ECs of automobile ACS operated in India and the UAE, especially in India, were more diverse than those in South Korea, China, and the United States (Fig. 1 and S1), which might be caused by the differences in environmental and climate factors such as temperature, humidity, and VOCs (3,4). Because the average temperatures for the year in India (Delhi) and the UAE (Dubai) are higher than those in South Korea (Namyangju and Ulsan), China (Beijing and Shanghai), and the United States (Irvine, CA), the operation times of automobile ACS in India and the UAE will also be longer than those in South Korea, China, and the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Opportunistic pathogens such as nontuberculous mycobacteria (NTM) and legionellae may enter cars via biofilms in car heaters/air conditioners (AC) (11,12) and in windshield washer reservoirs (13), as well as other sources (14)(15)(16). Even though many types of NTM are increasingly recognized as human pathogens (17)(18)(19), there is virtually no information on their recovery from inside the family car.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilms formed in car heaters/air conditioners [11, 12] as well as those in windshield washer reservoirs [13] and other areas of the car may release microbes such as legionellae and possibly environmental or nontuberculous mycobacteria (NTM) as well as airborne opportunistic pathogens. Such pathogens may also come from road dust and water in road puddles [14].…”
Section: Sources Of Microbes Their Allergens and Toxinsmentioning
confidence: 99%
“…An investigation on malodors associated with air-conditioning systems in automobiles found the heat exchanger fins of 45 evaporators from seven different regions of the world to be coated with biofilms [11]. The biofilms were analyzed and found to contain a wide variety of bacteria including potential human pathogens such as members of the genera Sphingomonadales, Burkholderiales, Bacillales, and Stenotrophomonas .…”
Section: Infectious Agents Of Concernmentioning
confidence: 99%